DEVELOPMENT OF COMIC MEDIA ON VIRUS MATERIALS FOR HIGH SCHOOL CLASS STUDENTS - Fitri Yati Kumil Laila (Universitas Islam Balitar, 2018)
The development was carried out aimed at finding out the feasibility of comic learning media in viral material for high school students of class X This research is a Research and Development study using a 4-D model (Define, Design, Develop, and Disseminate) limited to the Develop stage. The data taken from this study is based on the validation of material experts, media experts, linguists, and readability tests. The results of the validation by the expert team get an average score of 84.64% with proper information. Student readability test results are 90% high category with very decent information. According to the results outlined in the comic learning media, it is worthy of being used as a learning media for viral material.